Soccer Sam - Marzollo, Jean.; Sims, Blanche (New York : Random House, 1987)
Sam's cousin from Mexico comes for an extended visit and teaches Sam and all the second graders to play soccer.
Elem. School Library Collection
2.5
K-3
Keywords: Soccer -- Fiction; Mexicans -- United States -- Fiction; Soccer -- Fiction; Mexicans -- United States -- Fiction